Pengaruh Modal Kerja, Likuiditas, Leverage dan Volume Penjualan terhadap Profitabilitas Perusahaan Farmasi yang Terdaftar di BEI Periode 2016-2021 - Rofi'ah, Rofi'ah; Pranjoto, R. Gatot Heru (Jurnal Kajian Ilmu Manajemen (JKIM), 2023)
This study aims to determine and analyze the effect of Working Capital, Liquidity, Leverage, and Sales Volume both partially and simultaneously on Profitability in Pharmaceutical Companies listed on the Indonesia Stock Exchange (IDX) exchange for the 2016-2021 period. Samples were determined using purposive sampling techniques, with the specified criteria, the number of samples thus obtained are as many as 10 companies. The analytical method used in this research was multiple linear regression analysis to test the requirements, namely the classical assumption test through SPSS version 26.0. The Results show that (1) working capital has a positive and no significant effect on profitability; (2) liquidity has a positive and no significant effect on profitability. (3) leverage (DAR) has a negative and significant effect on profitability; (4) Leverage (DER) has a positive and no significant effect on profitability; (5) sales volume has a negative and no significant effect on profitability; (6) The variables of working capital, liquidity, leverage, and sales volume together or simultaneously have a significant effect on profitability.